2020
DOI: 10.1002/cam4.3148
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding RNA 886 alleviates tumor cellular immunological rejection in host C57BL/C mice

Abstract: Non‐coding RNA 886 (nc886/VTRNA2‐1) is a Pol III transcript and an atypical imprinted gene. Its exact function as a negative regulator of protein kinase R establishes its connection with innate immunity. Studies have shown that nc886 silencing is closely associated with prostate cancer progression. Previous work has constructed a cell model of stable nc886 overexpression (“mimic” or “nc886 + ”) in PC‐3M‐1E8 cell lines (1E8), which are highly bone‐metastatic human prostate cancer cells wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…This association agrees with its proposed roles in innate immune modulation via PKR repression or OAS1 regulation and in cytokine production (Calderon & Conn, 2018;Golec et al, 2019;Lee et al, 2020;Li et al, 2015). Furthermore, vtRNA2-1 has been associated with autoimmune disorders (Renauer et al, 2015;Weeding & Sawalha, 2018) and tumor engraftment in prostate cancer (Ma et al, 2020). This enrichment in viral infection pathways, together with the viral infection involvement of the core TFs common to all vtRNAs, reinforces the hypothesis of the re-utilization of a regulatory RNA induced upon viral response in favor of cancer development at upstream and downstream regulatory steps.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…This association agrees with its proposed roles in innate immune modulation via PKR repression or OAS1 regulation and in cytokine production (Calderon & Conn, 2018;Golec et al, 2019;Lee et al, 2020;Li et al, 2015). Furthermore, vtRNA2-1 has been associated with autoimmune disorders (Renauer et al, 2015;Weeding & Sawalha, 2018) and tumor engraftment in prostate cancer (Ma et al, 2020). This enrichment in viral infection pathways, together with the viral infection involvement of the core TFs common to all vtRNAs, reinforces the hypothesis of the re-utilization of a regulatory RNA induced upon viral response in favor of cancer development at upstream and downstream regulatory steps.…”
Section: Discussionsupporting
confidence: 72%
“…Due to its importance for cancer biology, vtRNA2-1 transcriptional regulation was recently more investigated (Yeganeh & Hernandez, 2020). Various studies reported tissue specific roles of vtRNA2-1 in normal (Golec et al, 2019;Lee et al, 2019;Miñones-Moyano et al, 2013;Sallustio et al, 2016;Suojalehto et al, 2014) and cancer tissues (Ahn et al, 2018;Fort et al, 2018;Hu et al, 2017;Im et al, 2020;Jeon et al, 2012a;Kunkeaw et al, 2012;Lee et al, 2011;Lee, 2015;Lee et al, 2014a;Lee et al, 2014b;Lee et al, 2016;Lei et al, 2017;Li et al, 2017;Ma et al, 2020;Treppendahl et al, 2012) and epigenetic alterations of the locus have been described in different malignancies (Ahn et al, 2018;Cao et al, 2013;Fort et al, 2018;Helbo et al, 2015;Helbo et al, 2017;Joo et al, 2018;Lee et al, 2014a;Lee et al, 2014b;Park et al, 2017a;Romanelli et al, 2014;Treppendahl et al, 2012). Meanwhile, except for Kirsten Grønbaek group´s contributions on the chromatin characterization of vtRNA1-3 and vtRNA1-2 promoters (Helbo et al, 2015;Helbo et al, 2017), little is known about the transcriptional regulation and expression of the other vtRNAs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, vtRNA2-1 was proposed as a new type of ncRNA functioning as a tumor suppressor gene (TSG) that inhibits PKR, and was consequently renamed as “nc886” ( Golec et al , 2019 ; Jeon et al , 2012a ; Jeon et al , 2012b ; Lee et al , 2011 ). Then, its anti-proliferative and TSG function was described in prostate ( Aakula et al , 2016 ; Fort et al , 2018 ; Ma et al , 2020 ), skin ( Lee et al , 2019a ), gastric ( Lee et al , 2014b ) esophageal ( Im et al , 2020 ; Lee et al , 2014a ) and cholangiocarcinoma cells ( Kunkeaw et al , 2012 ). Conversely, a pro-proliferative and anti-apoptotic oncogenic role was proposed for vtRNA2-1 in renal ( Lei et al , 2017 ), ovarian ( Ahn et al , 2018 ), thyroid ( Lee et al , 2016 ), cervical ( Li et al , 2017 ) and endometrial ( Hu et al , 2017 ) tissues.…”
Section: Introductionmentioning
confidence: 99%